ASSESING STUDENT PERPECTIVES : A SURVEY OF TEXTBOOK EVALUATION AMONG SOPHOMORE ENGLISH EDUCATION STUDENTS - Syahid, Abdul; Syamsyara , Amaliya; Niesrina , Maulida Zahrotun; Fitrian , Novia; Saumi , Rahma Ibtida; Wulandari , Widya (Jurnal Ilmiah Multidisiplin, 2024)
This study contains the evaluation of the textbook "Idiom Drills: For Students of English as a Second Language" based on the perceptions of five students of Tarbiyah Department of English at Institut Agama Islam Palangka Raya. The research method used for data collection was giving the physical book to five students, who were then evaluated using a questionnaire through Google Form and Tentative Checklist. The results of the analysis indicated that the book successfully met the learners' age-based usage needs, needs, and interests. The book is considered effective in vocabulary management, with the distribution of new words according to the level of learning difficulty. The book also offered a well-structured language learning experience, with tasks designed progressively from simple to complex, and using immersive natural language, which contributed to increased student engagement. However, the findings also identified some shortcomings in terms of unattractive layout, suboptimal use of text, and lack of additional support materials such as audio. The implication of these findings is the importance of enhancing and developing textbooks that are more effective and responsive to students' needs. It is, therefore, a valuable contribution to our understanding of textbook evaluation in the context of teaching English as a second language.